Computer Simulation of Flow Dynamics in an Intracranial Aneurysm: Effects of Vessel Wall Pulsation on a Case of Ophthalmic Aneurysm - Kobayashi, N. (Centauro S.r.l., 2004)
Using a supercomputer, the authors studied the effect of vessel wall pulsation on flow dynamics with a three-dimensional model simulating both a rigid and pulsatile style. The design of the aneurysm models was set with a 5 mm dome diameter and a 1 or 3 mm orifice size to simulate a carotid-ophthalmic aneurysm. Flow dynamics were analyzed according to flow pattern, wall pressure and wall shear stress. The flow pattern in the aneurysm sac showed the great difference between rigid and pulsatile models particularly in the small-neck aneurysm model. The arterial wall tended to be exposed to a higher pressure peak in the pulsatile model than in the rigid one, especially at its bifurcation and curved regions. Sites of shear stress peak were found on the aneurysmal dome as well as at the distal end of the orifice in both rigid and pulsatile models. The effects of vessel-wall pulsation should be considered whenever evaluating conditions in and around an aneurysm.